If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (V + -6)(v + -2) = 0 Reorder the terms: (-6 + V)(v + -2) = 0 Reorder the terms: (-6 + V)(-2 + v) = 0 Multiply (-6 + V) * (-2 + v) (-6(-2 + v) + V(-2 + v)) = 0 ((-2 * -6 + v * -6) + V(-2 + v)) = 0 ((12 + -6v) + V(-2 + v)) = 0 (12 + -6v + (-2 * V + v * V)) = 0 (12 + -6v + (-2V + vV)) = 0 Reorder the terms: (12 + -2V + -6v + vV) = 0 (12 + -2V + -6v + vV) = 0 Solving 12 + -2V + -6v + vV = 0 Solving for variable 'V'. Move all terms containing V to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -2V + -6v + -12 + vV = 0 + -12 Reorder the terms: 12 + -12 + -2V + -6v + vV = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -2V + -6v + vV = 0 + -12 -2V + -6v + vV = 0 + -12 Combine like terms: 0 + -12 = -12 -2V + -6v + vV = -12 Add '6v' to each side of the equation. -2V + -6v + 6v + vV = -12 + 6v Combine like terms: -6v + 6v = 0 -2V + 0 + vV = -12 + 6v -2V + vV = -12 + 6v Reorder the terms: 12 + -2V + -6v + vV = -12 + 6v + 12 + -6v Reorder the terms: 12 + -2V + -6v + vV = -12 + 12 + 6v + -6v Combine like terms: -12 + 12 = 0 12 + -2V + -6v + vV = 0 + 6v + -6v 12 + -2V + -6v + vV = 6v + -6v Combine like terms: 6v + -6v = 0 12 + -2V + -6v + vV = 0 The solution to this equation could not be determined.
| 4C^2-35C+49=0 | | -x+12.8=33.2 | | 9(t-6)+5t=7(2t+5)-8 | | (x-3)(x+7)=o | | 4x(3x+6)=2(x-7) | | 5n^2+7=132 | | 0.1(8)+x=0.4(8+x) | | 16x-100= | | 6y+9=39 | | x+89.6=57.3 | | 3m^2+3=51 | | 86a+43= | | 10y=100x+40fory | | N^2-10=-6 | | 6x-6y=48fory | | 5w+6y=15m | | 34x-6= | | N^2-3=78 | | 64y+28= | | 10x+6(80)=8x+8(80) | | -4x+5=.6 | | 8x+y-11=0 | | 6(x+5)-(6x+30)= | | -7d+3+5(d+2)=7d+3+5d+10 | | -2x-7x=-(2x-1)+6(x+2) | | 21+9x= | | X^2-12x+30=-5 | | X^2*2X+10=4 | | 8x-9=x-2 | | 3x+-1y=2 | | 22+14z= | | 13p-6=7p+12 |